Stereotactic arrhythmia radioablation: a multicenter pre-post intervention safety evaluation of the implantable cardioverter-defibrillator function - Ree, Martijn H. van der; Hoeksema, Wiert F.; Luca, Adrian; Visser, Jorrit; Balgobind, Brian V.; Zumbrink, Michiel; Spier, Raymond; Herrera-Siklody, Claudia; Lee, Justin; Bates, Matthew; Daniel, Jim; Peedell, Clive; et al. (Radiotherapy and oncology, 2023)
Background - Stereotactic arrhythmia radioablation (STAR) appears to be beneficial in selected patients with therapy-refractory ventricular tachycardia (VT). However, high-dose radiotherapy used for STAR-treatment may affect functioning of the patients’ implantable cardioverter defibrillator (ICD) by direct effects of radiation on ICD components or cardiac tissue. Currently, the effect of STAR on ICD functioning remains unknown. - Methods - A retrospective pre-post multicenter study evaluating ICD functioning in the 12-month before and after STAR was performed. Patients with (non)ischemic cardiomyopathies with therapy-refractory VT and ICD who underwent STAR were included and the occurrence of ICD-related adverse events was collected. Evaluated ICD parameters included sensing, capture threshold and impedance. A linear mixed-effects model was used to investigate the association between STAR, radiotherapy dose and changes in lead parameters over time. - Results - In total, 43 patients (88% male) were included in this study. All patients had an ICD with an additional right atrial lead in 34 (79%) and a ventricular lead in 17 (40%) patients. Median ICD-generator dose was 0.1 Gy and lead tip dose ranged from 0-32 Gy. In one patient (2%), a reset occurred during treatment, but otherwise, STAR and radiotherapy dose were not associated with clinically relevant alterations in ICD leads parameters. - Conclusions - STAR treatment did not result in major ICD malfunction. Only one radiotherapy related adverse event occurred during the study follow-up without patient harm. No clinically relevant alterations in ICD functioning were observed after STAR in any of the leads. With the reported doses STAR appears to be safe.